1994
DOI: 10.1152/ajpheart.1994.267.4.h1630
|View full text |Cite
|
Sign up to set email alerts
|

Stretch-mediated activation of cardiac renin gene

Abstract: This study was designed to quantitate cardiac mRNA levels encoding components of the local renin-angiotensin system during the development of volume overload-induced cardiac hypertrophy. Changes in cardiac renin mRNA levels were measured in relation to renin activity in the left ventricle (LV) and in plasma after acute passive stretch of the heart caused by an aortovenocaval shunt in the rat. A quantitative reverse-transcriptase polymerase chain reaction method with competitive internal standards was used to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

1996
1996
2000
2000

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…Each HPLC fraction was 300 l. Aliquots (100-l) of each relevant fraction of column effluent were subjected to RIA immediately upon collection. Elution of standard ANG peptides under isocratic conditions revealed clear resolution of ANG I, II, and III and ANG [1][2][3][4][5][6][7] and ANG 3-8 peptides. RIA of relevant peaks revealed detectable levels of ANG I and II in all plasma and ISF samples examined.…”
Section: Biochemical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Each HPLC fraction was 300 l. Aliquots (100-l) of each relevant fraction of column effluent were subjected to RIA immediately upon collection. Elution of standard ANG peptides under isocratic conditions revealed clear resolution of ANG I, II, and III and ANG [1][2][3][4][5][6][7] and ANG 3-8 peptides. RIA of relevant peaks revealed detectable levels of ANG I and II in all plasma and ISF samples examined.…”
Section: Biochemical Analysesmentioning
confidence: 99%
“…Components of the renin-angiotensin system (RAS) have been demonstrated in the heart by biochemical, immunohistochemical, and molecular biological techniques (4). Increased gene transcript levels of the components of the RAS, including renin (5), angiotensinogen (6), angiotensin receptors (7), and angiotensin-converting enzyme (ACE) (8)(9)(10) have been identified in experimental models of pressure (6)(7)(8) and volume overload (5,9,10) in the rat heart. Thus, there is increasing evidence that ANG II formation in the heart is mediated by a local RAS, acts independently of the circulating RAS components, and is upregulated by hemodynamic stress.…”
Section: Introductionmentioning
confidence: 99%
“…Volume overload, as a result of aortocaval shunt, is associated with increased expression of renin 54 and ACE, but not Ao or AT 1 , in cardiac ventricles. 54,55 This is in contrast to pressure overload of the myocardium, in which there is increased expression of Ao and AT 1 mRNA in the left ventricle.…”
Section: Regulation Of the Cardiac Ras In The Failing Heartmentioning
confidence: 96%
“…No change in cardiac angiotensinogen mRNA was found in the volumeoverload model. 54,66 In contrast, Lindpaintner et al 65 reported a transient activation of angiotensinogen mRNA in the noninfarcted left ventricle of rats after a coronary artery ligation. Part of these discrepancies might be related to the inflammatory response that will occur after myocardial infarction but not after the induction of volume overload.…”
Section: Ang II Synthesis In the Heart Under Pathological Conditionsmentioning
confidence: 97%
“…Renin mRNA levels in normal hearts are low or undetectable, [52][53][54] and the cardiac levels of renin, Ang I, and Ang II decrease in parallel with the plasma levels of these RAS components to levels close to or below the detection limit after a bilateral nephrectomy. 47,55 Furthermore, renin and angiotensins cannot be demonstrated in the perfusate of the isolated Langendorff-perfused rat heart 56,57 or in the supernatant of serum-deprived neonatal rat cardiomyocytes.…”
Section: Ang II Synthesis In the Heart Under Normal Conditionsmentioning
confidence: 99%